2012
DOI: 10.1002/chem.201202655
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic‐Carbene‐Catalyzed Reaction of α‐Bromo‐α,β‐Unsaturated Aldehyde or α,β‐Dibromoaldehyde with Isatins: An Efficient Synthesis of Spirocyclic Oxindole–Dihydropyranones

Abstract: Smooth as isatin! A straightforward synthesis of spirocyclic oxindole–dihydropyranones through an N‐heterocyclic‐carbene‐catalyzed [4+2] annulation of α‐bromo‐α,β‐unsaturated aldehydes or α,β‐dibromoaldehyde bearing γ‐H with isatin derivatives under mild reaction conditions is disclosed (see scheme). The concise construction, ready availability of the starting materials, avoidance of external oxidants, and the potential utilization value of final products in molecular biology and pharmacy makes this approach p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…In addition, α,β‐unsaturated δ‐lactones are a part of a wide variety of natural scaffolds, for example, fostriecin, callystatin, ( R )‐goniothalamin, asperlin, leptomycin B and kazusamycin A,20 or serve as intermediates in the synthesis of bioactive molecules, such as tetrahydrolipstatin21 and clavulactone 22. Owing to their importance, many methods have been developed for their synthesis, such as the hetero‐Diels–Alder (HDA) reactions of the Brassard diene with aldehydes or ketones,2326 solid‐phase Diels–Alder cycloaddition,27 the annulation of open‐chain precursors,28 N‐heterocyclic‐carbene‐catalysed reactions of α‐bromo α,β‐unsaturated aldehydes,29 reactions of homoallylic alcohols with the lithium enolate of methyl acetate30 and enzymatic cyclisation31 (Figure 1). Intriguingly, most of these methods suffer from poor enantioselectivity and substrate scope, and often employ environmentally hazardous metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, α,β‐unsaturated δ‐lactones are a part of a wide variety of natural scaffolds, for example, fostriecin, callystatin, ( R )‐goniothalamin, asperlin, leptomycin B and kazusamycin A,20 or serve as intermediates in the synthesis of bioactive molecules, such as tetrahydrolipstatin21 and clavulactone 22. Owing to their importance, many methods have been developed for their synthesis, such as the hetero‐Diels–Alder (HDA) reactions of the Brassard diene with aldehydes or ketones,2326 solid‐phase Diels–Alder cycloaddition,27 the annulation of open‐chain precursors,28 N‐heterocyclic‐carbene‐catalysed reactions of α‐bromo α,β‐unsaturated aldehydes,29 reactions of homoallylic alcohols with the lithium enolate of methyl acetate30 and enzymatic cyclisation31 (Figure 1). Intriguingly, most of these methods suffer from poor enantioselectivity and substrate scope, and often employ environmentally hazardous metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…( Table 2, entry 1), while electron rich 2,4-(CH 3 O) 2 C 6 H 3 and 4-(CH 3 ) 2 NC 6 H 4 gave 6e and 6f in 99:1 e.r. [18] Va riation of the ester was examined with methyl, isopropyl, and allyl esters (6i, 6j and 6k)p repared with excellent enantiopurity (98:2, 94:6 and 99:1 e.r.) Ther eaction tolerated N-heterocycles with indole-containing b-lactone 6h prepared in 83 %y ield and 98:2 e.r.…”
mentioning
confidence: 99%
“…Unfortunately, b-alkyl acyl fluorides were not compatible with the reaction, potentially due to acyl azolium dienolate formation as developed by Chi and others with related substrates. ( Table 1, entries [16][17][18]. [10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] In 2012, Chi et al reported a pioneering oxidative NHCcatalyzed [4+2] annulation of enals with trifluoromethyl ketones by g addition (Scheme 1 a). [8] We envisioned that the addition of an NHC to enals having a g leaving group may generate a dienolate intermediate, which would then react with an azodicarboxylate to give the [4+2] annulation product (Scheme 1 c). [8] We envisioned that the addition of an NHC to enals having a g leaving group may generate a dienolate intermediate, which would then react with an azodicarboxylate to give the [4+2] annulation product (Scheme 1 c).…”
mentioning
confidence: 99%